Self‐Powered Colloidal Wurtzite‐Structure Quantum Dots Photodetectors Based On Photoinduced‐Pyroelectric Effect. Issue 21 (29th August 2018) - Jin, Lufan; Zhang, Yating; Yu, Yu; Chen, Zhiliang; Li, Yifan; Cao, Mingxuan; Che, Yongli; Yao, Jianquan
Abstract: Colloidal wurtzite‐structure CdSe/ZnS quantum dots (CWQDs), with noncentral asymmetry structure and spontaneous polarization, have an extensive potential for applications based on the pyroelectric effect, such as energy harvestors, self‐powered nanogenerators, and photosensors. Here, a low‐cost, easy‐fabrication, and high‐speed self‐powered photodetector is demonstrated, which performs independently without any external power source. The response of the device caused by the photoinduced‐pyroelectric effect is experimentally investigated based on the Au/CWQDs/Au edge‐electrodes structure, which exhibits an ultrafast photoresponse with a rising time of 20.6 µs and a falling time of 30.1 µs. Moreover, the frequency and temperature dependence of the device also is investigated under zero bias. This work provides a new approach to achieve self‐powered photodetectors, which may show promise for extensive batch applications, such as wireless sensing, optothermal detection, optoelectronic communication, and energy harvesting. Abstract : Self‐powered photodetectors based on colloidal wurtzite‐structure CdSe/ZnS quantum dots show excellent photoinduced‐pyroelectric performance without any external power source. The potential converting ambient energy into electric energy meets the growing energy demand. The solution‐based process, low cost, and ultrafast response time of these photodetectors may contribute to advancements in wireless sensing, photothermal detection, optoelectronic communication, and energy harvesting.